“My lecturer’s expressionless face kills me!” An evaluation of learning process of German language class in Indonesia - Primardiana Hermilia Wijayati; Rofi'ah Rofi'ah; Ahmad Fauzi Mohd Ayub (REID (Research and Evaluation in Education), 2018)
This qualitative study aimed at evaluating the circumstances in plenary class that provoke learners’ speaking anxiety. To meet the objectives, this study investigated students of German as a Foreign Language (GFL) course who were experiencing speaking anxiety symptoms in the plenary class. The research was a narrative qualitative study, and the data were collected through observation and interview. The result of this study reveals that learners’ speaking anxiety occurred in particular circumstances of the plenary class, such as unfamiliar topic, still class, students’ unpreparedness for spontaneous speaking, expressionless face of the lecturer, and students’ fear of native speaker lecturers.